Coaching track & field successfully - Guthrie, Mark (Human Kinetics, 2003)
When it comes to building a top-notch track and field program, performance is only part of the picture. From training and motivation on the field to planning and organizing behind the scenes, Coaching Track & Field Successfully offers a comprehensive guide to getting your program up to speed. Season planning. Event coaching. Meet preparation. Postmeet analysis. Athlete-coach communication. This book covers all the issues a coach must effectively address in building and maintaining a championship program. How do you motivate players? What's your philosophy of coaching? How can you communicate your vision to athletes, parents, and critical members of the coaching team? With Coaching Track & Field Successfully, you'll learn all of that and much more from someone who's been through it all. Since 1986 Mark Guthrie has coached the University of Wisconsin at La Crosse teams to 17 Division III national championships. Before that he was a high school coach with the skill, insight, and drive to lead his school to three consecutive state cross country championship victories. Now he presents proven techniques to pack more power into your program. Guthrie teaches the essential techniques of the sport, provides simple training programs, and presents a wealth of vital information required for building a quality team. His teaching progressions, event-specific technical instruction, and tips on planning for big events make Coaching Track & Field Successfully the critical resource coaches need to take their teams to the top.